Most neutralizing human monoclonal antibodies target novel epitopes requiring both Lassa virus glycoprotein subunits - James E. Robinson (Nature Portfolio, 2016)
Lassa virus can cause haemorrhagic fever for which no specific treatment currently exists. Here the authors have cloned 113 monoclonal antibodies from the survivors of Lassa infection and show that the majority of neutralizing antibodies target a complex of GP1 and GP2 viral proteins.